The debt prison: The effect of court-ordered monetary sanctions on recidivism - Tostlebe, Jennifer Jewel (2017)
The use of monetary sanctions as part of the punishment process has been a part of the American criminal justice system since colonization. However, there has been little empirical research investigating the effect of financial penalties incurred by criminal offenders and the extent to which such sanctions relate to the likelihood of recidivism. By applying General Strain Theory, this study explores how monetary sanctions, along with demographics and prior offense type, affect the recidivism rates of persons who were incarcerated. Utilizing a sample of 729 first-time prisoners released from Iowa prisons and then followed for three years, secondary data from the Iowa Department of Corrections is paired with self-collected monetary sanction data from Iowa Courts Online to test the hypothesis that court-ordered monetary sanctions affect the recidivism of first-time prisoners in Iowa. Logistic regression analyses suggest there is not a statistically significant association between monetary sanctions and recidivism. However, ROC curve analysis suggests there is an association between monetary sanctions and recidivism. The results also suggest higher total sanction amount decreases time to recidivism, while higher restitution amount increases time to recidivism